2018
DOI: 10.3390/computers7040057
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Framework for Portfolio Selection Model Using Modified ANFIS and Fuzzy Sets

Abstract: This paper proposes a novel framework for solving the portfolio selection problem. This framework is excogitated using two newly parameters obtained from an existing basic mean variance model. The scheme can prove entirely advantageous for decision-making while using computed values of these significant parameters. The framework combines effectiveness of the mean-variance model and another significant parameter called Conditional-Value-at-Risk (CVaR). It focuses on extracting two newly parameters viz. αnew and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Modification of the adaptive neuro-fuzzy inference system (ANFIS) was proposed in [5] as a tool. The proposal deserves special attention due to the introduction at the early stages of a model of an additional control element based on fuzzy logic.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…Modification of the adaptive neuro-fuzzy inference system (ANFIS) was proposed in [5] as a tool. The proposal deserves special attention due to the introduction at the early stages of a model of an additional control element based on fuzzy logic.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…London et al [23] investigated the Markowitz PS problem and implemented several estimators to determine the expected return of a portfolio. Kumar and Doja [24] and then Wei et al [25] showed that the feasibility of replacing expert subjectiveness with knowledge based on the given information.…”
Section: Introductionmentioning
confidence: 99%
“…Over time, Markowitz's theory has been extended and improved by different approaches to modeling uncertainty. Fuzzy sets have been widely employed in portfolio optimization because the uncertainty of return can be easily quantified by fuzzy variables [2,3]. Recently, the neutrosophic theory, which extends the fuzzy concept, has been applied for solving portfolio selection problems [4] and for characterization of both portfolio performance indicators: return and risk [5].…”
Section: Introductionmentioning
confidence: 99%